The Multifarious Nature of Literary Studies - KALANTARYAN, ZHENYA (Bulletin of Yerevan University B: Philology, 2021)
Based on vast amounts of data, this article analyses various perceptions of literary studies and the object of its study – literature. Throughout history, changing perspectives of literary studies and literature have led to different and sometimes even contradictive methods of analysis. The variety of research methods in literary studies is also determined by the multifarious nature of literature, as well as the need to elucidate its different sides. This article attempts to show that literary studies ― irrespective of its diversity ― has retained its entirety. It is also noted that moral and humanistic criteria, which are characteristic of the humanities, are often ignored in contemporary scientific discourse analysis. The present study concludes that literary studies are subject to ongoing development, and as historical experience shows, transformations in this process should not be ruled out.